2013
DOI: 10.1128/jvi.00471-13
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Hemagglutinin Trimerization Completes Monomer Folding and Antigenicity

Abstract: c Influenza A virus (IAV) remains an important human pathogen largely because of antigenic drift, the rapid emergence of antibody escape mutants that precludes durable vaccination. The most potent neutralizing antibodies interact with cognate epitopes in the globular "head" domain of hemagglutinin (HA), a homotrimeric glycoprotein. The H1 HA possesses five distinct regions defined by a large number of mouse monoclonal antibodies (MAbs), i.e., Ca1, Ca2, Cb, Sa, and Sb. Ca1-Ca2 sites require HA trimerization to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 44 publications
(55 reference statements)
9
63
0
Order By: Relevance
“…Neutralization assays confirmed that the P234K mutation escaped H17-L10, while the P234V mutation caused no change in antibody sensitivity (Fig 5B). Interestingly, in HA's structure, site 234 is on a neighboring protomer relative to all the other mutations strongly selected by H17-L10 (S2 Fig). Our finding that escape mutations from H17-L10 cross the HA trimer interface is consistent with the fact that this antibody only recognizes trimeric HA [41]. Escape mutations at such epitopes are discernible because mutational antigenic profiling uses actual viruses that display intact HA; such conformational epitopes might not be properly displayed in the modified forms of viral glycoproteins often used in other high-throughput methods such as phage and yeast display.…”
Section: Comparison To Traditional Neutralization Assayssupporting
confidence: 81%
“…Neutralization assays confirmed that the P234K mutation escaped H17-L10, while the P234V mutation caused no change in antibody sensitivity (Fig 5B). Interestingly, in HA's structure, site 234 is on a neighboring protomer relative to all the other mutations strongly selected by H17-L10 (S2 Fig). Our finding that escape mutations from H17-L10 cross the HA trimer interface is consistent with the fact that this antibody only recognizes trimeric HA [41]. Escape mutations at such epitopes are discernible because mutational antigenic profiling uses actual viruses that display intact HA; such conformational epitopes might not be properly displayed in the modified forms of viral glycoproteins often used in other high-throughput methods such as phage and yeast display.…”
Section: Comparison To Traditional Neutralization Assayssupporting
confidence: 81%
“…All Abs used are mouse IgG mAbs and have been described previously (Brooke et al , 2013; Gerhard et al , 1981; Magadan et al , 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The selection criteria included: 1 ) conservation among H1, H2, H3, and H5 subtypes; 2 ) sites containing ≥6 residues as a minimum length required for a peptide to elicit an antibody response; and 3 ) sites where >50% residues had a conservation score of 0.9–1.0 calculated from multiple sequence alignment. Previously, Sahini et al (10) used the monomer conformation of H3 (PDB: 1HGJ), but here, we used the trimer structure as a more-relevant conformation for the present purpose, considering that influenza HA is a homotrimeric membrane glycoprotein, and some antigenic sites require HA trimerization (39). To determine whether the predicted sites are suitable for binding to their specific antibodies, structural characteristics, such as accessible surface area and polarity, were analyzed in HA trimers ( Fig.…”
Section: Resultsmentioning
confidence: 99%